Gnome 2 as a Donor of Short Stem Characteristic for Winter Rye (Secale cereale L.). - В. В. Скорик (Plant Varieties Studying and Protection)
Stabilizing (centripetal) breeding produced donor of short stem characteristic for winter rye (Secale cereale L.) with height of plants ranging from cm 50 to 60. Distribution curve of plant's height remained symmetric with cummulation of frequencies at central classes (leptokurtic). For the first time, designation for new allele of short-stem gene HI-2HI-2 and donor name Gnome 2 was suggested. Gnome 2 was found to have direct genetic correlation of plant height with number of flowers in the ear, length of the ear, weight of 100 seeds from the plant, as well as reverse correlation with ear density and weight of kernels from the ear.